2014
DOI: 10.1515/ijfe-2012-0095
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of the Quantity and Particle Size of Wheat Bran on Some Properties of Bread Dough using Response Surface Methodology

Abstract: The aim of this study was to find empirical models for some properties of bread dough as a function of bran concentration and particle size using D-Optimal made by Design Expert Software. Wheat flour was replaced with 0, 5, 10, 15 and 20% (w/w, flour basis) wheat bran at particle sizes of 170, 280, 425 and 750 μm. Increasing bran concentration and particle size enhanced dough water absorption. Dough arrival and development times increased, while dough stability time, tolerance to mixing and volume rising decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…1.0 and 1.3 min, respectively. This is confirmed by the study carried out by Majzoobi et al (2014), who demonstrated the impact of the coarser granulation of wheat bran on the prolongation of the time of bread dough development. In turn, fibres with several-fold smaller particle diameters (D[4,3]), in particular carob and apple fibres, exhibited the greatest arm slopes (R MAXp1 , R MINp1 ) and the highest peaks p 1 (C Fp1 ) up to ca.…”
Section: Rheological Characteristics Of Fibre Supplementssupporting
confidence: 67%
“…1.0 and 1.3 min, respectively. This is confirmed by the study carried out by Majzoobi et al (2014), who demonstrated the impact of the coarser granulation of wheat bran on the prolongation of the time of bread dough development. In turn, fibres with several-fold smaller particle diameters (D[4,3]), in particular carob and apple fibres, exhibited the greatest arm slopes (R MAXp1 , R MINp1 ) and the highest peaks p 1 (C Fp1 ) up to ca.…”
Section: Rheological Characteristics Of Fibre Supplementssupporting
confidence: 67%
“…Compared with the other fractions of the soybean hull, BB samples, at both levels (20% and 30%) with the largest particle size, recorded the least stability time and the maximum degree of softening after 12 min (Table S2 ). The size elevating of the soybean hull particles probably prevented gluten network creation and subsequently the stability time shortening (Majzoobi et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The weakening of the gluten network and the interaction between the fiber and the protein network are the reasons for this reduction (Noort et al, 2010). In the literature, the reported results regarding the effect of wheat bran particle size on the final quality of bread are different and even contradictory (López et al, 2004; Majzoobi et al, 2014; Noort et al, 2010; Rosell, 2011). Unlike wheat bran, which is problematic to be ground finely and produces fractions with different sizes and physicochemical and nutritional properties—soybean hull is much easier to be ground.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the results showed an increase ( p < 0.05) in bread hardness due to the inclusion of oat flour with greater particle sizes and higher inclusion levels of oat flour fractions, as it ranged from 398.87 g (in 10 F 4) in comparison to 1227.38 g (in 50 F 3). The increased crumb hardness is attributed to the dilution of the gluten network and increased dietary fiber content that impairs gas retention, resulting in a lower bread volume and a firmer texture (Majzoobi et al., 2014). Additionally, as stated before, the reason for increasing water absorption, particularly in the F 1 and F 2 flour fractions, can be attributed to the increase in surface area in the samples with small particle sizes, particularly for the starch‐rich fraction of oat flour used.…”
Section: Resultsmentioning
confidence: 99%